Inflammatory pseudotumours of the oesophagus – histological and immunohistochemical findings. Issue 7 (20th January 2015) - Sy, Keiyan; Parfitt, Jeremy; Marginean, Celia; Riddell, Robert H; Streutker, Catherine J
Abstract : Aims: Inflammatory oesophageal pseudotumours are rare lesions, thought to be reactive. Due to marked atypia of the stromal cells, these can be misdiagnosed as malignancies. The objective of this study was to characterize histological and immunohistochemical features of a series of inflammatory pseudotumours of the oesophagus. Methods and results: We present 12 cases of inflammatory oesophageal pseudotumours, occurring in seven females and five males, with a mean age of 57.3 years. Clinical presentations were variable; dysphagia, abdominal pain and weight loss and upper gastrointestinal bleed. In a majority of the cases, nodules or masses in the distal oesophagus were identified at endoscopy. Microscopically, the lamina propria in all 12 cases contained inflammation and granulation tissue. Ten of 12 cases showed mucosal ulceration and 11 of 12 cases had acutely inflamed epithelium. Markedly atypical pleomorphic stromal cells with prominent nucleoli were identified in all 12 cases. Immunohistochemistry showed uniform positivity for vimentin in 11 of 11 cases, and two of seven cases demonstrated weak focal positivity for smooth muscle actin. The cells were negative for all other markers. Conclusions: Reactive oesophageal lesions can show marked nuclear atypia in stromal fibroblasts/myofibroblasts, which are easily mistaken for malignancies. Pathologists must consider the diagnosis of an inflammatory pseudotumour if stromal atypia is present in an inflammatory background.